HAK BEKERJA BAGI PENYANDANG CACAT DITINJAU DARI KONSTITUSI INDONESIA - Sekar Anggun Gading Pinilih (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2016)
Discrimination against persons with disabilities has major implications on their difficulty to obtain amenity, such as finding a job, get health insurance and social, educational guarantees, political rights and much more. The discriminatory treatment is a violation of the human rights of persons with disabilities, both vertically (by agents of the State against citizens or otherwise) or horizontally (between citizens themselves). The Indonesian Constitution recognizes the equality of every person to get a job and a way of life, regardless of social status and legal status attached to each individual, as expressed in Article 28 A through Article 28 A of the Constitution of 1945.